Conversion from rural settlements and arable land under rapid urbanization in Beijing during 1985–2010. (April 2017) - Liu, Yansui; Yang, Yuanyuan; Li, Yurui; Li, Jintao
Abstract: With significant economic development over the last several decades in China, urban land has increasingly sprawled and encroached upon arable land and rural settlements. In this context, this paper explores the dynamic spatiotemporal characteristics and trends of rural settlement loss and arable land depletion in the process of urban expansion, which could offer a theoretical basis and scientific support for further research of rural development and restructuring. The conclusions of the study are summarized as follows: (1) approximately 80% of urban growth has been at the expense of rural settlements (23.42%) and arable land (57.14%) in Beijing; and (2) an obvious rural non-agriculturization-intensive belt was observed in spatial units from 1985 to 2010, primarily distributed between the Fourth Ring Road and the Fifth Ring Road. Non-agriculturization is defined here as the conversion of land formerly used for agricultural purposes, including rural settlements and arable land, to more densely developed urban uses. (3) The spatial distribution of fastest, fast and medium non-agriculturization began to shift from the northern area to the southern area after 2005. (4) The curves of variation of rural non-agriculturization intensity under urbanization along the urban-rural gradient presented as inverted "U" shapes leading away from the socioeconomic center, while that along the motorways displayed exponential decay. Adhering to the policy of urbanization strategy will be essential for rural restructuring in China. Highlights: Spatiotemporal characteristics of rural settlements loss and arable land depletion during urbanization was explored. Different degrees of rural non-agriculturalization were zoned. Spatial modes of rural non-agriculturalization along the urban-rural gradient and the motorways were proposed.